One question at a time!: A text mining analysis of the ECB Q&A session - Siria Angino; Robert Robitu (European Central Bank (ECB), 2023)
News media play a fundamental role in the communication between central banks and the public. Besides stimulating institutional transparency, the reporting of the news media on a central bank's activities is also the main source of information about the institution for most citizens. To better understand how this intermediation process works, this paper explores the Q&A session of the European Central Bank (ECB)'s press conferences, where journalists have an opportunity to set the discussion and inquire into the central bank's thinking. Using a structural topic model on a novel dataset consisting of all questions asked at ECB press conferences since May 2012, we conduct a systematic examination of the topics the ECB is questioned about and uncover differences in the focus of outlets from different geographical areas and with different types of audiences. We find that international outlets devote more attention to technical topics, relevant for market participants, while domestic media in the European Union (EU) dedicate greater focus to national affairs and the more political dimensions of the ECB's activities.
Keywords: E52; E58; E59; 330; Central bank communication; European Central Bank; media; Structural Topic Modelling